CREATIVITY IN ORGANIZATIONS AND ITS IMPACT IN THE INDUSTRY OF HOSPITALITY: APPLIED STUDY - Assistant Professor Dr. Amal Kamal Hassan Al Baraznji (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Many business organizations are witnessing a remarkable development in building creative thought and in several sectors, including tourism, in addition to an increase in the intensity of competition in the hospitality industry to become more exploiting of various opportunities and to ensure its stability and continued growth. Creativity can be considered as the best method and strategic way for business success as well as facing the risks and problems that may be exposed to it.